Co-expression network analysis reveals PbTGA4 and PbAPRR2 as core transcription factors of drought response in an important timber species Phoebe bournei - Yu, Jinjian; Yin, Ke; Liu, Yan; Li, Yuhui; Zhang, Junhong; Han, Xiao; Tong, Zaikang (Frontiers in Plant Science, 2024)
Phoebe bournei is one of the main afforestation tree species in subtropical regions of China and is famous for its timber. Its distribution and growth are significantly impaired by water conditions. Thus, it is essential to understand the mechanism of the stress response in P. bournei. Here, we analyzed the phenotypic changes and transcriptomic rearrangement in the leaves and roots of P. bournei seedlings grown for 0 h, 1 h, 24 h, and 72 h under simulated drought conditions (10% PEG 6000). The results showed that drought stress inhibited plant photosynthesis and increased oxidoreductase activity and abscisic acid (ABA) accumulation. Spatio-temporal transcriptomic analysis identified 2836 and 3704 differentially expressed genes (DEGs) in leaves and roots, respectively.The responsive genes in different organs presented various expression profiles at different times. Gene co-expression network analysis identified two core transcription factors, TGA4 and APRR2, from two modules that showed a strong positive correlation with ABA accumulation. Our study investigated the different responses of aboveground and belowground organs of P. bournei to drought stress and provides critical information for improving the drought resistance of this timber species.